The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fped.2022.872900
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intranasal Dexmedetomidine vs. Oral Chloral Hydrate for Sedation in Children Undergoing Computed Tomography/Magnetic Resonance Imaging: A Meta-Analysis

Abstract: ObjectiveThis meta-analysis aims to evaluate the sedative efficacy and safety of intranasal administration of dexmedetomidine (DEX) compared with oral chloral hydrate for Computed tomography (CT) or Magnetic Resonance Imaging (MRI) examination in Children.MethodsCochrane Library, PubMed, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), and China WanFang Databases were searched to collect randomized controlled trials (RCTs) investigating intranasal DEX (test group) vs. oral chloral hydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…However, some studies have shown that Dex has an effect on the cardiovascular system and could be responsible for lowering the heart rate and blood pressure, while the effect on the respiratory rate and saturation is less common ( 21 , 24 26 , 34 39 ). Nevertheless, our findings are in line with several studies which have demonstrated, that Dex is safe to use in children undergoing EEG ( 40 42 ). However, awareness of the possible adverse reactions is essential to prevent potential complications.…”
Section: Discussionsupporting
confidence: 92%
“…However, some studies have shown that Dex has an effect on the cardiovascular system and could be responsible for lowering the heart rate and blood pressure, while the effect on the respiratory rate and saturation is less common ( 21 , 24 26 , 34 39 ). Nevertheless, our findings are in line with several studies which have demonstrated, that Dex is safe to use in children undergoing EEG ( 40 42 ). However, awareness of the possible adverse reactions is essential to prevent potential complications.…”
Section: Discussionsupporting
confidence: 92%
“…It is convenient, effective, and does not cause respiratory depression which maximizes the benefits for the pediatric population ( 6 , 7 ). A meta-analysis revealed that intranasal dexmedetomidine was superior to traditional oral chloral hydrate and could provide better safety for imaging sedation ( 8 ). On the other hand, dexmedetomidine has the unique capability to create a neurophysiological state similar to non-rapid-eye-movement sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Another investigations compared intranasal dexmedetomidine to oral chloral hydrate, an hypnotic sedative often administered in nurse-assisted diagnostic procedures due to its safe profile [37]. Dexmedetomidine resulted in higher procedural success rate (RR = 1.14, 95% CI 1.03 to 1.26), faster awaking (–9.75 min, 95% CI –17.57 to –1.94) and lower incidence of nausea and vomiting (RR = 0.09, 95% CI 0.04 to 0.23) than chloral hydrate.…”
Section: Nurse-assisted Sedated Magnetic Resonance Imagingmentioning
confidence: 99%